Facial Nerve Function Outcome and Risk Factors in Resection of Large Cystic Vestibular Schwannomas - Stastna, Daniela; Mannion, Richard; Axon, Patrick; Moffat, David Andrew; Donnelly, Neil; Tysome, James R.; Hardy, David G.; Bance, Mahonar; Joannides, Alexis; Lawes, Indu; Macfarlane, Robert (Journal of Neurological Surgery Part B: Skull Base, 2021)
Objective Cystic vestibular schwannomas (VS) in contrast to solid VS tend to have accelerated growth, larger volume, rapid/atypical presentation, lobulated/adherent surface, and unpredictable course of the cranial nerves. Cystic VS are surgically challenging, with worse clinical outcomes and higher rate of subtotal resection (STR).Methods We retrospectively analyzed postoperative outcomes of 125 patients with cystic VS, operated between years 2005 and 2019 in our center. We confronted the extent of the resection and House-Brackmann (HB) grade of facial palsy with the results of comparable cohort of patients with solid VS operated in our center and literature review by Thakur et al.1Results Translabyrinthine approach was preferred for resection of large, cystic VS (97.6%). Gross-total resection (GTR) was achieved in 78 patients (62.4%), near-total resection (NTR) with remnant (<4 × 4 × 2 mm) in 43 patients (34.4%), and STR in 4 patients (3.2%). NTR/STR were significantly associated with higher age, tumor volume >5 cm3, retrosigmoid approach, high-riding jugular bulb, tumor adherence to the brain stem, and facial nerve (p = 0.016; 0.003; 0.005; 0.025; 0.001; and <0.00001, respectively).One year after the surgery, 76% of patients had HB grades 1 to 2, 16% had HB grades 3 to 4, and 8% had HB grades 5 to 6 palsy. Worse outcome (HB grades 3 to 6) was associated with preoperative facial palsy, tumor volume >25 cm3, and cyst over the brain stem (p = 0.045; 0.014; and 0.05, respectively). Comparable solid VS operated in our center had significantly higher HB grades 1 to 2 rate than our cystic VS (94% versus 76%; p = 0.03). Comparing our results with literature review, our HB grades 1 to 2 rate was significantly higher (76% versus 39%; p = 0.0001). Tumor control rate 5 years after surgery was 95.8%.Conclusion Our study confirmed that microsurgery of cystic VS has worse outcomes of facial nerve preservation and extent of resection compared with solid VS. Greater attention should be paid to the above-mentioned risk factors.
Keywords: cystic vestibular schwannoma; microsurgery; facial nerve outcome; near-total resection; long-term outcome